indonesia Clustering Daerah Penyebaran Covid-19 Di Indonesia Menggunakan Algoritma K-Medoids - Husdi; Muis Nanja (KITA Institute, 2022)
The year 2019 was the beginning of the outbreak of a disease that hit the world today called the Covid-19 Virus. The virus originated from Wuhan and is now designated as a pandemic. The main problem raised in this study is how to determine the spread of covid-19 in Indonesia based on provincial data. Because there are several areas that have high prevalence cases, it is necessary to improve health services and protocols in these areas compared to areas with rather low distribution areas. So that in this study a clustering method is needed to be able to classify data on the spread of COVID-19 in Indonesia. The algorithm used for clustering is the K-Medoids algorithm. Based on the results of the research conducted, the K-Medoids Method is able to group the Covid 19 Spreading Areas in Indonesia.